A Gender-Stylistics Approach to Ninotchka Rosca - Layno, Jose Virgilio R. (College of Arts and Letters, University of the Philippines Diliman, 1987)
This was done in the light of the problem of an existent female mode of writing that is distinct from the male one, given a male-dominated set-up where literary language, conventions and forms are shaped by masculine biases, taking Ninotchka Rosca as the representative author for feminine gender. In answering the problem, six hypotheses regarding male/female language were tackled, namely: 1) Women tend to use more evaluative and emotive words than men, specifically adjectives; 2) Women are more color sensitive than men; 3) Women make greater use of adverbs of intensity/degree than men while men tend to avoid them; 4) Women are more perceptive to their environment than men; 5) Women's sentences are prolix; and 6) Women are fond of coordination and the loose paratactic construction. The first four hypotheses fall under lexis while the last two fall under syntax. Since fourth hypothesis was not directly referable to observable linguistic features, this writer has chosen to include nouns of body parts to stand for "environment". The sample texts used for this specific study were from the following stories: "The Southern Seas", "The Seventh Circle", "A Parable of Evil", "Bitter Country", "Words of Wisdom", "Generations", "The Goddess", and "Of Your Intense Fragility". This study also made use of the relative norm or the analyses of D.H. Lawrence and Henry James to serve as masculine constants to illustrate the stylistic differences peculiar to each gender. The sample text for Lawrence is "Odour of Chrysanthemums", and for James, "The Pupil". The hypotheses were generally confirmed, save for prolixity of sentence. However, it was shown that the author has achieved "subliminal prolixity", in the binary method of investigation. Using the same approach, the study inquired into the feminineness or gynotextuality of the author. It is revealed that she has used a lot of words that were associated with women, and used a lot of nouns, adjectives, and coinages that have feminine valency. The study, on the whole, supported that the central hypothesis that gender is a crucial determinant in the creation of literary discourses is, indeed, tenable.